The Implementation of Knowledge Management System in Enhancing University Performance and Competitiveness - Rosalin, Sovia; Rudiyanto, San (Universitas Negeri Makassar, 2024)
In the era of globalization and digitalization, universities play a crucial role as centers of knowledge development and innovation. Thus, knowledge management becomes a critical aspect in maintaining the sustainability, efficiency, and competitiveness of universities. A Knowledge Management System (KMS) is a solution that can support the management, dissemination, and utilization of knowledge within universities in a more systematic and integrated manner. Universities store and produce knowledge in various forms, whether from research, teaching, or practical experience. However, without proper management, this knowledge is often scattered and not fully utilized. A Knowledge Management System (KMS) is expected to help consolidate this knowledge into a single system that is easily accessible to the entire academic community, whether for learning, research, or institutional development purposes. This article aims to describe the Knowledge Management System (KMS) process at the Vocational Faculty of Universitas Brawijaya. The article employs a case study research type with a qualitative approach. A total of 15 informants were involved, consisting of faculty leaders, department heads, program directors, and lecturers at the Vocational Faculty of Universitas Brawijaya. The research findings indicate that a systematic Knowledge Management System (KMS) has not yet been implemented at the Vocational Faculty of Universitas Brawijaya, highlighting the need to establish a comprehensive KMS to improve the work system and the quality of human resources at the Vocational Faculty of Universitas Brawijaya.